Using NDN in improving energy efﬁciency of MANET - Muchtar, Farkhana; Kumar Singh, Pradeep; Alubady, Raaid; Mohd Nordin, Ili Najaa Aimi (Springer Nature, 2020)
This paper seeks to extol the virtues of named data networking (NDN), as an alternative to host-centric networking (HCN), for its prominent features that can be taken advantage of to significantly reduce energy consumption demands in a mobile ad hoc network (MANET) implementation. Therefore, a NDN-based content routing mechanism was compared with two types of HCN routing protocol implementations in this study: OLSR and Batman-adv. The experimental results obtained from this research provide early evidence that NDN can increase the energy efficiency of MANETcompared to the use ofHCNprimarily TCP/IP on the network stack solution for MANET. Of particular note would be NDN-based content routing’s viability as a solution for energy consumption issues that plague wireless multi-hop ad hoc networks. Last but not least, this paper also provides the future research direction that could be undertaken on the subject.